2018
DOI: 10.1080/10934529.2018.1471024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the cytotoxicity of tin dioxide nanofibers

Abstract: Tin dioxide nanofibers (SnDNFs) are small fibers that have many applications. Tin dioxide nanofibers can be used in cosmetics, solar cells, toxic gas release sensors, and air pollution control. To date there have been few studies on the cytotoxicity of SnDNFs. The goal of this research is to determine if electrospun SnDNFs are toxic in a lung cancer cell line (A549). Considering the nano-scale size of the fibers, they can easily be inhaled and enter the pulmonary system and cause toxic effects in the lung. Occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…The specific surface area, total pore volume and average pore size of the fibers were 41 m 2 g −1 , 0.15 cm 3 g −1 and 10 nm, respectively. The surface area of the fibers is somewhat higher than that found in literature for both dense 51 and hollow 56,62 electrospun SnO 2 fibers calcined at 500 or 600 °C, 6.9 to 36 m 2 g −1 . The same is true of the total pore volume, as a smaller pore volume of 0.079 cm 3 g −1 has been reported by Mudra et al 62 while a larger average pore size of 16 nm has been reported by Xia et al 56 The surface area of the SnO 2 fibers is quite high considering the large 71 nm crystallites, as large crystallites commonly result in a small surface area.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…The specific surface area, total pore volume and average pore size of the fibers were 41 m 2 g −1 , 0.15 cm 3 g −1 and 10 nm, respectively. The surface area of the fibers is somewhat higher than that found in literature for both dense 51 and hollow 56,62 electrospun SnO 2 fibers calcined at 500 or 600 °C, 6.9 to 36 m 2 g −1 . The same is true of the total pore volume, as a smaller pore volume of 0.079 cm 3 g −1 has been reported by Mudra et al 62 while a larger average pore size of 16 nm has been reported by Xia et al 56 The surface area of the SnO 2 fibers is quite high considering the large 71 nm crystallites, as large crystallites commonly result in a small surface area.…”
Section: Resultscontrasting
confidence: 65%
“…This feed rate is 4 to 500 times as high as reported for the electrospinning of SnO 2 and SnO 2 /SiO 2 bers. [21][22][23][24]26,50,51 The needle was pushed through a 3 mm metal adapter of a box enclosing a cylindrical side collector and a planar back collector at 80 cm distance, both being made of a metal wire mesh. The potential difference between the needle and collectors was set to 15 kV with a high voltage power source, and compressed air was delivered through the adapter at a rate of 30 NL min À1 .…”
mentioning
confidence: 99%
“…[14,30,37] We observed that this NM produces inflammation and induces pulmonary, hepatic and systemic APR in mice, as shown by the increased levels of neutrophils and plasma SAA3, almost as high as our benchmark materials (TiO 2 and Printex 90). In vitro studies with SnO 2 NM have shown that this material decreases cell viability, affects cell membrane structure and increases reactive oxygen species (ROS) production in different cancer cell lines, including a human lung adenorcarcinoma cell line (A549) [69][70][71]. A recent study compared the effects of SnO 2 and TiO 2 NM on A549 cell and murine monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Half-maximal cytotoxic concentration (in mM) of various cationic species: Li [428,429,430], Na [431,432,433,434], Mg [435,436,437,438], Sr [439,440,441], Al [442,443,444], Ga [408,445], Sn [406,446,447], Te [448,449,450], Pb [427,451], Bi [452,453,454,455], Ti [406,408,443,444,456,457], V [408,442,443,444], Cr [408,442,443,444], Mn [443,458,459,460], Fe [426,442,443,461], Co [406,408,442,443,444,462,463], Ni [406,408,430,443,…”
Section: Figurementioning
confidence: 99%